Decolorization of Direct Blue Dye by Electrocoagulation Process - Ghali Attia, Hadi (Journal of Engineering and Sustainable Development, 2013)
Electrocoagulation (EC) was tested as an alternative method for the satisfactory removal of direct blue dye from an aqueous medium. Batch EC studies were performed using Iron electrodes to evaluate the influence of various experimental parameters, i.e., Initial pH: 2-10, current density (CD): 25-250 A/m2, electrolysis time (t): 2-10 min, and initial concentration (CO): 25 – 200 mg/L, on the removal of direct blue dye. Additionally, the effects of these parameters on electrical energy consumption were studied under the optimum conditions. The results showed that 98.71 % of direct blue was decolorized and 1.7 KWh/m3 of energy consumed for an initial dye concentration of 100 mg/L with the current density of 200 A/m2, solution conductivity of 1.16 ms/cm, at room temperature of approximately 298±2 K, an interelectrode distance of 1.5 cm, and initial pH of 4 at the end of 6 min of time of electrolysis.